2003
DOI: 10.1039/b308951g
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic investigation of speciation in MgSO4(aq)

Abstract: Careful measurements have been made of the Raman spectra of aqueous solutions of Mg(ClO 4 ) 2 , MgCl 2 , (NH 4 ) 2 SO 4 and MgSO 4 down to 50 cm -1 and, in some cases, to extremely low concentrations (≥0.0006 mol/kg) and high temperatures (≤200 °C). In MgSO 4 (aq), the well known asymmetry in the ν 1 -SO 4 2-mode at ~980 cm -1 that develops with increasing concentration has been assigned to a mode at 993 cm -1 associated with the formation of an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
220
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(245 citation statements)
references
References 58 publications
23
220
2
Order By: Relevance
“…In other words, UO2 2+ and SO4 2-are highly associated in the Urich phase. This is in line with previous studies suggesting that the ion association increases with increasing sulfate concentration [21,43].…”
Section: Uo2so4 Concentration Of the Immiscible Fluidssupporting
confidence: 82%
See 4 more Smart Citations
“…In other words, UO2 2+ and SO4 2-are highly associated in the Urich phase. This is in line with previous studies suggesting that the ion association increases with increasing sulfate concentration [21,43].…”
Section: Uo2so4 Concentration Of the Immiscible Fluidssupporting
confidence: 82%
“…1015 and 1028 cm -1 . It has been reported that the v1(SO4 2-) band becomes broader and the wavenumber increases with the increase of the length of inner-sphere ion pairs in aqueous MgSO4 solution [21,23,[35][36]. Considering the obvious higher-wavenumber shift of the v1(SO4 2-) band (Fig.…”
Section: Ion Association Between Uo2 2+ and So4 2-mentioning
confidence: 99%
See 3 more Smart Citations